Jamaica. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Jamaica during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as agrotourism, slaughterhouses, infrastructure, phytosanitary, standards, production, greenhouse, rural development, research, packaging, leadership, and marketing. Finally, work was done on decision-making, fishing, post-harvest handling, information management, pig farming, and the value chains of ginger, tomato, lobster, and bell pepper.